Do not put all your eggs in one basket: social perspectives on desalination and water recycling in Israel. Issue 11 (2nd November 2022) - Sneegas, Gretchen; Seghezzo, Lucas; Brannstrom, Christian; Jepson, Wendy; Eckstein, Gabriel
Abstract: Israel has set ambitious goals in terms of the widespread adoption of desalination and water recycling technologies. Policymakers in Israel consider these technologies as the key to improve urban water security but knowledge of stakeholder views on this policy approach is not well established. We deployed the Q-methodology, a qualitative–quantitative approach, to empirically determine social perspectives on desalination and water recycling across a wide range of stakeholders in the Israeli water sector. We identified the following four distinctive social perspectives: (1) desalination should be the option of last resort; (2) desalination is moving us to an infinite resource; (3) equating savings to resources is a dangerous illusion; and (4) desalination is (risky) electric water. A common characteristic of these perspectives is the belief that desalination is necessary for a water-secure country, but desalination should not be the only source of drinking water in Israel. Our findings indicate that Israeli stakeholders show complex and contingent understandings of the pros and cons of desalination and water recycling and the risks involved in too much reliance on a limited number of water sources. We discuss the potential implications of our findings for water management and security in Israel and other places with water scarcity concerns. HIGHLIGHTS: Using the Q-method, we identified four social perspectives on desalination and water recycling in Israel. Stakeholders believe that desalination provides water security, but it should not be the only water source. Stakeholders focus on the positive and negative aspects of water practices. The link between desalination and peace was a point of contention. Israeli stakeholders understand the pros and cons of desalination and water recycling.